BioModels’ Model of the Year 2023 - Malik Sheriff, Rahuman S.; Asari, Hiroki; Hermjakob, Henning; Huber, Wolfgang; Quail, Thomas; Santos, Silvia D. M.; Smith, Amber M.; Uhlmann, Virginie (Frontiers in Systems Biology, 2024)
Mathematical modelling is a pivotal tool in deciphering the complexities of biological systems and their control mechanisms, providing substantial benefits for industrial applications, and answering relevant biological questions. The BioModels' Model of the Year 2023 competition was established to recognize and highlight exciting modelling-based research in life science, particularly by nonindependent early career researchers. It further aims to endorse reproducibility and FAIR principles of model sharing among these researchers. This article delineates the competition's criteria for participation and selection, introduces the award recipients, and provides an overview of their contribution. Their models provide crucial insights into cell division regulation, protein stability, and cell fate determination, illustrating the role of mathematical modelling in advancing biological research.